Pendampingan Manajemen Risiko Kesehatan Mental Anak Sekolah Akibat Bullying - Andi Sri Adinda; Nursuciyani Jamal (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Primary education is crucial for child development, especially at the elementary school level. Children begin to acquire various basic knowledge that will shape their cognitive, social, and emotional abilities. However, reality shows that schools can also become sites of aggressive behavior in the form of bullying. According to the Ministry of Women’s Empowerment and Child Protection (2023), cases of bullying in elementary schools have shown an increasing trend over the past five years. The purpose of this activity is to broaden students' understanding of bullying and its impacts, foster empathy and mutual respect, and strengthen the roles of teachers and parents in creating a safe and inclusive school environment. Findings indicate the presence of students who still lack understanding regarding types of bullying, with a high category showing that some individuals remain frequent targets of bullying. This may be caused by factors such as physical differences, social status, family background, or weak social support from peers. This condition indicates that schools still need to implement preventive and intervention approaches to protect students who are vulnerable to bullying.